Full‐color‐tunable chiral aggregation‐induced emission fluorophores with tailored propeller chirality and their circularly polarized luminescence - Yifan Li; Junhao Liang; Shiwei Fu; Haoxin Huang; Sheng Liu; Lei Wang; Yi Liu (Aggregate)
Abstract The regulation of emission color, emission efficiency, and asymmetry factor is of great significance for the real applications of circularly polarized luminescent (CPL) materials. Herein, we develop a modular synthetic strategy toward full‐color‐tunable CPL materials based on chiral macrocyclic aggregation‐induced emission (AIE) luminogens via delicate molecular engineering. Modular synthesis of chiral AIEgens with different acceptor moieties has afforded a series of bright solid emitters with tunable emission colors. These chiral cyclic AIEgens have retained high solid‐state emission quantum yield and displayed CPL emission from blue to red as nano‐aggregates, in liquid crystal matrix and polymer film. The strong acceptor units in the red‐emitting chiral AIEgens RBTPE‐2CN and SBTPE‐2CN have rendered them twisted intramolecular charge transfer properties and solvatochromic luminescence. And polymer matrix with different polarity further facilitates the tuning of CPL emission color from green to red emission. These results have paved a reliable approach toward constructing full‐spectra solid‐state CPL material.